Electromagnetic waves and radiating systems - Acharyya, Parimal (Aryan Pub. House, 2011)
Electromagnetic waves and radiating systems / Acharyya, Parimal. -- Kolkata: Aryan Pub. House, 2011 539.2 Ac176 No. of Copies : 6